Performance regulation and control method for hole structure of laser 3D printing high-entropy alloy support
Through laser 3D printing technology, the pore structure and process parameters of high-entropy alloy scaffolds were optimized, combined with first-principle calculation and sol-gel method, porous hydroxyapatite/high-entropy alloy composite materials with excellent mechanical properties and good biocompatibility were prepared, which solved the problem of unclear influence mechanisms of the mechanical properties and biocompatibility of high-entropy alloy materials, and achieved accurate control and performance improvement of the material.
Patent Information
- Application Number
- CN202411535538.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-14
AI Technical Summary
The mechanism of the influence of high-entropy alloy component selection and pore structure design on its mechanical properties and adhesion properties to hydroxyapatite is unclear.
Through laser 3D printing technology, the pore structure and process parameters of high-entropy alloy scaffolds are optimized, and combined with first-principle calculation and sol-gel method, porous hydroxyapatite/high-entropy alloy composite materials with excellent mechanical properties and good biocompatibility are prepared.
Accurate control of the pore structure of high-entropy alloy materials is achieved, improving its strength, toughness and fatigue properties, and ensuring corrosion resistance and biocompatibility in the physiological environment.
Smart Images

Figure CN119609160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a performance control method for a laser 3D printed high entropy alloy bracket pore structure, and belongs to the field of high entropy alloys. Background Art
[0002] Hydroxyapatite / high entropy alloy porous composite biomaterials fully combine the advantages of high entropy alloys' high strength and wear resistance and hydroxyapatite's excellent biocompatibility, and are a type of implantable biomaterial with great application prospects. However, the mechanism of how the selection of high entropy alloy components and their pore structure design affect their mechanical properties and adhesion properties with hydroxyapatite is still unclear. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for controlling the performance of the pore structure of a laser 3D printed high entropy alloy stent to solve the problems raised in the above background technology.
[0004] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for controlling the performance of a laser 3D printed high entropy alloy stent pore structure, comprising the following steps:
[0005] Step 1: Composition design and mechanical properties study of medical high entropy alloys;
[0006] Focus on the design and synthesis of high-entropy alloys of key metal elements, combine first-principles calculation methods to analyze the physical mechanisms that affect the hardness, strength and elastic modulus of materials, provide theoretical guidance for the synthesis of high-entropy alloy materials with excellent mechanical properties, optimize the microstructure and phase composition of the alloy, and conduct systematic mechanical property tests on the synthesized high-entropy alloys. Based on existing commercial implant biomaterials, evaluate the key mechanical indicators of the alloy, such as strength, toughness, and hardness;
[0007] Step 2: Pore structure and performance regulation of laser 3D printed high entropy alloy stents;
[0008] By combining experiments and simulations, the process parameters of laser 3D printing are optimized to achieve the solidification of the preparation process parameters of porous high-entropy alloy materials. By optimizing the printing path strategy and post-processing technology, the porosity, pore size and connectivity of the porous high-entropy alloy are precisely controlled to obtain a high-entropy alloy scaffold with a highly customized porous structure. Through mechanical testing, the strength, toughness and fatigue properties of the printed porous high-entropy alloy are evaluated to reveal the correlation mechanism between the composition and pore structure of the whole material and the mechanical properties.
[0009] Step 3: Preparation and biocompatibility evaluation of hydroxyapatite / high entropy alloy composites;
[0010] The sol-gel method is used to achieve effective coating of hydroxyapatite on the surface of high entropy alloy. The preparation of hydroxyapatite / high entropy alloy composites with uniform structure and complete coating is achieved by regulating the precursor concentration, temperature, pH value and aging time parameters. The mechanical properties of porous hydroxyapatite / high entropy alloy composites are evaluated by compression test, three-point bending test and other methods, and compared with the mechanical properties of human hard tissue to determine its feasibility for hard tissue repair. The corrosion resistance of porous hydroxyapatite / high entropy alloy composites in physiological environment is evaluated by simulated body fluid immersion experiment and electrochemical impedance spectroscopy to ensure its stability during long-term implantation in the body.
[0011] Specifically, in step 1, the key metal elements in the alloy are determined, different component ratios are designed to explore the effects of different element combinations on the properties of the alloy, the electronic structure of the alloy is calculated using the basic principles of quantum mechanics and solid physics, the total energy, electronic state density, and band structure of the alloy are calculated, the designed alloy is synthesized by mechanical alloying, and the microstructure of the alloy is observed using a transmission electron microscope and a scanning electron microscope. Tensile tests, compression tests, and hardness tests are performed to evaluate the mechanical properties of the alloy, experimental data and first-principles calculation results are analyzed, factors affecting hardness, strength, and elastic modulus are explored, and the effects of the interaction of alloy elements, lattice distortion, solid solution strengthening, etc. on the performance are studied. According to the experimental and calculation results, the alloy composition and preparation process are adjusted to optimize the alloy performance, the experiments and calculations are repeated on the optimized alloy composition to verify the effect of the improvement, all experimental data and calculation results are integrated, and a comprehensive data analysis is performed. According to the theoretical analysis results, the subsequent alloy synthesis and performance optimization are guided.
[0012] Specifically, in step 2, the laser power, scanning speed and layer thickness of laser 3D printing are optimized, the printing path mode is changed, the influence of different paths on the pore structure is observed, and post-processing technology optimization experiments are carried out, including heat treatment temperature range and holding time. By adjusting the above process parameters, the porosity is controlled, and pore size and connectivity control experiments are carried out. Subsequently, the samples are subjected to compression tests, three-point bending tests and fatigue tests, and the influence of alloy composition on pore structure and mechanical properties is studied by changing the alloy composition. The laser 3D printing process is simulated by finite element analysis, compared with experimental data, and the process parameters are optimized. The strength, toughness and fatigue properties of the printed porous high entropy alloy are evaluated, revealing the association mechanism between the whole material composition and pore structure and mechanical properties.
[0013] Specifically, in step 3, the hydroxyapatite / high entropy alloy composite material is first prepared by a sol-gel method, the precursor concentration is adjusted to prepare a hydroxyapatite precursor sol, the prepared porous high entropy alloy stent is fully immersed in the hydroxyapatite precursor solution, the pH value of the solution is adjusted and the reaction temperature is controlled to achieve the conversion of the precursor sol to the hydroxyapatite coating, and X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques are used to evaluate the coating uniformity and integrity of the hydroxyapatite, collect mechanical property data of human hard tissue, compare the compression modulus and flexural strength parameters of the hydroxyapatite / high entropy alloy composite material with those of human hard tissue, immerse the composite material in simulated body fluid, take out the thickness regularly to test its mass loss and surface morphology changes, and perform an electrochemical impedance spectroscopy test in the simulated body fluid, set the frequency range, and comprehensively evaluate the stability, corrosion resistance and biocompatibility of the composite biomaterial.
[0014] Beneficial effects of the present invention:
[0015] Based on a deep understanding of the physical and chemical changes designed in the laser 3D printing process, a correlation mechanism between process parameters and macro / microstructure is established to achieve precise control of the pore structure of high-entropy alloy materials with key metal components.
[0016] Combined with first-principles calculations, a component optimization theory for key metal high-entropy alloy materials with the application goal of human implantable biomaterials is established, thereby achieving on-demand preparation of high-entropy alloy materials with high strength, high hardness and low elastic modulus. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0018] Figure 1 It is a technical roadmap of the performance control method of the laser 3D printing high entropy alloy bracket pore structure of the present invention; DETAILED DESCRIPTION
[0019] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0020] See also Figure 1 The present invention provides a technical solution: a method for controlling the performance of a high entropy alloy stent pore structure by laser 3D printing, comprising the following steps:
[0021] Step 1: Composition design and mechanical properties study of medical high entropy alloys;
[0022] Focus on the design and synthesis of high entropy alloys of key metal elements (Ti, Nb, Ta, Cr, Hf, etc.), combine the first-principles calculation method to analyze the physical mechanism that affects the hardness, strength and elastic modulus of the material, provide theoretical guidance for the synthesis of high entropy alloy materials with excellent mechanical properties, optimize the microstructure and phase composition of the alloy, and conduct systematic mechanical property tests on the synthesized high entropy alloys. Based on the existing commercial implant biomaterials, evaluate the key mechanical indicators of the alloy such as strength, toughness, hardness, etc.
[0023] Step 2: Pore structure and performance regulation of laser 3D printed high entropy alloy stents;
[0024] By combining experiments and simulations, the process parameters of laser 3D printing (such as laser power, scanning speed and layer thickness) are optimized to achieve the solidification of the preparation process parameters of porous high-entropy alloy materials. By optimizing the printing path strategy and post-processing technology, the porosity, pore size and connectivity of the porous high-entropy alloy are precisely controlled to obtain a high-entropy alloy scaffold with a highly customized porous structure. Through mechanical testing, the strength, toughness and fatigue properties of the printed porous high-entropy alloy are evaluated to reveal the correlation mechanism between the composition and pore structure of the whole material and the mechanical properties.
[0025] Step 3: Preparation and biocompatibility evaluation of hydroxyapatite / high entropy alloy composites;
[0026] The sol-gel method is used to achieve effective coating of hydroxyapatite on the surface of high entropy alloy. The preparation of hydroxyapatite / high entropy alloy composites with uniform structure and complete coating is achieved by regulating the precursor concentration, temperature, pH value and aging time parameters. The mechanical properties of porous hydroxyapatite / high entropy alloy composites are evaluated by compression test, three-point bending test and other methods, and compared with the mechanical properties of human hard tissue to determine its feasibility for hard tissue repair. The corrosion resistance of porous hydroxyapatite / high entropy alloy composites in physiological environment is evaluated by simulated body fluid immersion experiment and electrochemical impedance spectroscopy to ensure its stability during long-term implantation in the body.
[0027] In step 1, the key metal elements in the alloy, such as titanium (Ti), niobium (Nb), tantalum (Ta), chromium (Cr) and hafnium (Hf), are determined, and different component ratios are designed to explore the effects of different element combinations on the properties of the alloy. The electronic structure of the alloy is calculated using the basic principles of quantum mechanics and solid physics. The total energy, electronic state density and band structure of the alloy are calculated. The designed alloy is synthesized by mechanical alloying method, and the microstructure of the alloy is observed using transmission electron microscopy and scanning electron microscopy. Tensile tests, compression tests and hardness tests are performed to evaluate the mechanical properties of the alloy. The experimental data and first-principles calculation results are analyzed to explore the factors affecting hardness, strength and elastic modulus, and the effects of the interaction of alloy elements, lattice distortion, solid solution strengthening, etc. on the performance are studied. According to the experimental and calculation results, the alloy composition and preparation process are adjusted to optimize the alloy performance. The experiments and calculations are repeated on the optimized alloy composition to verify the effect of the improvement. All experimental data and calculation results are integrated to conduct a comprehensive data analysis. According to the theoretical analysis results, the subsequent alloy synthesis and performance optimization are guided.
[0028] In step 2, the laser power, scanning speed and layer thickness of laser 3D printing are optimized, and the printing path mode is changed, such as straight line, spiral or zigzag, to observe the influence of different paths on the pore structure, and conduct post-processing technology optimization experiments, including heat treatment temperature range and holding time. By adjusting the above process parameters, the porosity is controlled, and pore size and connectivity control experiments are conducted. Subsequently, the samples are subjected to compression test, three-point bending test and fatigue test, and the influence of alloy composition (adjusting the ratio of Ti, Zr, Co, Mg, Nb and Ta) on pore structure and mechanical properties is studied. The laser 3D printing process is simulated by finite element analysis, compared with experimental data, and the process parameters are optimized. The strength, toughness and fatigue properties of the printed porous high-entropy alloy are evaluated, revealing the association mechanism between the whole material composition and pore structure and mechanical properties.
[0029] In step 3, the hydroxyapatite / high entropy alloy composite material is first prepared by the sol-gel method, the precursor concentration is adjusted to prepare the hydroxyapatite precursor sol, the prepared porous high entropy alloy scaffold is fully immersed in the hydroxyapatite precursor solution, the pH value of the solution is adjusted and the reaction temperature is controlled to achieve the conversion of the precursor sol to the hydroxyapatite coating, and the coating uniformity and integrity of the hydroxyapatite are evaluated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques, and the mechanical properties data of human hard tissues (such as bones) are collected, and the compression modulus and flexural strength parameters of the hydroxyapatite / high entropy alloy composite material and the human hard tissue are compared. The composite material is immersed in simulated body fluid, and the mass loss and surface morphology changes are tested regularly. Electrochemical impedance spectroscopy is tested in simulated body fluid, and the frequency range is set to comprehensively evaluate the stability, corrosion resistance and biocompatibility of the composite biomaterial.
[0030] In the laser 3D printing process, laser power, scanning speed and layer thickness are key parameters, which together determine the degree of melting, pore structure and mechanical properties. By adjusting these parameters, the pore size, porosity and connectivity can be precisely controlled. For example, increasing the laser power can increase the degree of melting, thereby affecting the formation of pores; adjusting the scanning speed can change the size and shape of the molten pool, thereby affecting the morphology of the pores; changing the layer thickness will affect the density and accuracy of the print. Different printing path patterns (such as straight, spiral or zigzag) will lead to different heat distribution and molten pool dynamics, thereby affecting the formation and connectivity of pores. By changing the printing path pattern, the pore structure can be optimized and the mechanical properties can be improved. Therefore, the pore structure and performance regulation of porous high-entropy alloys by laser 3D printing and the preparation of porous hydroxyapatite / high-entropy alloy composite biomaterials are feasible. By optimizing laser 3D printing parameters, printing path patterns and post-processing techniques, the pore structure can be precisely controlled and the mechanical properties can be improved.
[0031] The sol-gel method is a commonly used method for preparing hydroxyapatite coatings, which can provide uniform coatings and good biocompatibility. By adjusting the precursor concentration, solution pH and reaction temperature, the formation and properties of the hydroxyapatite coating can be precisely controlled. The prepared porous high-entropy alloy stent is immersed in a hydroxyapatite precursor solution, and the conversion of the precursor sol to the hydroxyapatite coating can be achieved by regulating the solution pH and reaction temperature. In this way, a porous high-entropy alloy stent with a hydroxyapatite coating can be prepared, thereby improving its biocompatibility and bioactivity. Therefore, it is feasible to prepare high-performance porous hydroxyapatite / high-entropy alloy composite biomaterials by a sol-gel process.
[0032] Most of the phase analysis, microstructure and mechanical properties analysis methods of the synthesized hydroxyapatite / high entropy alloy composites can be tested according to national standards, and the test methods are mature and feasible. For the qualitative test of the corrosion resistance of the synthetic material, a simulated body fluid immersion experiment can be used. Specifically, the porous hydroxyapatite / high entropy alloy composite is immersed in simulated body fluid, and the corrosion of the material is observed to evaluate its stability in long-term implantation in the body. At the same time, electrochemical impedance spectroscopy (EIS) can be used to qualitatively evaluate the corrosion behavior of the material in the electrolyte solution. By measuring the impedance value of the material, the corrosion mechanism of the composite material can be revealed.
[0033] Based on a deep understanding of the physical and chemical changes designed in the laser 3D printing process, a correlation mechanism between process parameters and macro / microstructure is established to achieve precise control of the pore structure of high-entropy alloy materials with key metal components. Combined with first-principles calculations, a component optimization theory for key metal high-entropy alloy materials with the application goal of human implantable biomaterials is established to achieve on-demand preparation of high-entropy alloy materials with high strength, high hardness and low elastic modulus.
[0034] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for controlling the performance of a high entropy alloy stent pore structure by laser 3D printing, characterized in that The following steps are involved: Step 1: Composition design and mechanical properties study of medical high entropy alloys; Focus on the design and synthesis of high-entropy alloys of key metal elements, combine first-principles calculation methods to analyze the physical mechanisms that affect the hardness, strength and elastic modulus of materials, provide theoretical guidance for the synthesis of high-entropy alloy materials with excellent mechanical properties, optimize the microstructure and phase composition of the alloy, and conduct systematic mechanical property tests on the synthesized high-entropy alloys. Based on existing commercial implant biomaterials, evaluate the key mechanical indicators of the alloy, such as strength, toughness, and hardness; Step 2: Pore structure and performance regulation of laser 3D printed high entropy alloy stents; By combining experiments and simulations, the process parameters of laser 3D printing are optimized to achieve the solidification of the preparation process parameters of porous high-entropy alloy materials. By optimizing the printing path strategy and post-processing technology, the porosity, pore size and connectivity of the porous high-entropy alloy are precisely controlled to obtain a high-entropy alloy scaffold with a highly customized porous structure. Through mechanical testing, the strength, toughness and fatigue properties of the printed porous high-entropy alloy are evaluated to reveal the correlation mechanism between the composition and pore structure of the whole material and the mechanical properties. Step 3: Preparation and biocompatibility evaluation of hydroxyapatite / high entropy alloy composites; The sol-gel method is used to achieve effective coating of hydroxyapatite on the surface of high entropy alloy. The preparation of hydroxyapatite / high entropy alloy composites with uniform structure and complete coating is achieved by regulating the precursor concentration, temperature, pH value and aging time parameters. The mechanical properties of porous hydroxyapatite / high entropy alloy composites are evaluated by compression test, three-point bending test and other methods, and compared with the mechanical properties of human hard tissue to determine its feasibility for hard tissue repair. The corrosion resistance of porous hydroxyapatite / high entropy alloy composites in physiological environment is evaluated by simulated body fluid immersion experiment and electrochemical impedance spectroscopy to ensure its stability during long-term implantation in the body.
2. The method for controlling the performance of the pore structure of a laser 3D printed high entropy alloy stent according to claim 1, characterized in that: In the step 1, the key metal elements in the alloy are determined, different component ratios are designed to explore the effects of different element combinations on the properties of the alloy, the electronic structure of the alloy is calculated using the basic principles of quantum mechanics and solid physics, the total energy, electronic state density, and band structure of the alloy are calculated, the designed alloy is synthesized by mechanical alloying, and the microstructure of the alloy is observed using a transmission electron microscope and a scanning electron microscope. Tensile tests, compression tests, and hardness tests are performed to evaluate the mechanical properties of the alloy, and experimental data and first-principles calculation results are analyzed to explore factors affecting hardness, strength, and elastic modulus. The effects of the interaction of alloy elements, lattice distortion, solid solution strengthening, etc. on the properties are studied. According to the experimental and calculation results, the alloy composition and preparation process are adjusted to optimize the alloy properties, the experiments and calculations are repeated on the optimized alloy composition to verify the effect of the improvement, all experimental data and calculation results are integrated, and a comprehensive data analysis is performed. According to the theoretical analysis results, the subsequent alloy synthesis and performance optimization are guided.
3. The method for controlling the performance of the pore structure of a laser 3D printed high entropy alloy stent according to claim 1, characterized in that: In step 2, the laser power, scanning speed and layer thickness of laser 3D printing are optimized, the printing path mode is changed, the influence of different paths on the pore structure is observed, and post-processing technology optimization experiments are carried out, including heat treatment temperature range and holding time. By adjusting the above process parameters, the porosity is controlled, and pore size and connectivity control experiments are carried out. Subsequently, the samples are subjected to compression test, three-point bending test and fatigue test, and the influence of alloy composition on pore structure and mechanical properties is studied by changing the alloy composition. The laser 3D printing process is simulated by finite element analysis, compared with experimental data, and the process parameters are optimized. The strength, toughness and fatigue properties of the printed porous high entropy alloy are evaluated, revealing the association mechanism between the whole material composition and pore structure and mechanical properties.
4. The method for controlling the performance of the pore structure of a laser 3D printed high entropy alloy stent according to claim 1, characterized in that: In step 3, the hydroxyapatite / high entropy alloy composite material is first prepared by a sol-gel method, the precursor concentration is adjusted to prepare a hydroxyapatite precursor sol, the prepared porous high entropy alloy stent is fully immersed in the hydroxyapatite precursor solution, the pH value of the solution is adjusted and the reaction temperature is controlled to achieve the conversion of the precursor sol to the hydroxyapatite coating, and X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques are used to evaluate the coating uniformity and integrity of the hydroxyapatite, collect mechanical property data of human hard tissue, compare the compression modulus and flexural strength parameters of the hydroxyapatite / high entropy alloy composite material with those of human hard tissue, immerse the composite material in simulated body fluid, take out the thickness regularly to test its mass loss and surface morphology changes, and perform an electrochemical impedance spectroscopy test in the simulated body fluid, set the frequency range, and comprehensively evaluate the stability, corrosion resistance and biocompatibility of the composite biomaterial.
Citation Information
Cited By
High-entropy ceramic phase change reinforced silver-based electric contact material component screening method
CN119993350A
A Component Screening Method for High-Entropy Ceramic Phase-Transformation Strengthened Silver-Based Electrical Contact Materials
CN119993350B